Ant circadian activity associated with brood care type. (28th February 2017) - Fujioka, Haruna; Abe, Masato S.; Fuchikawa, Taro; Tsuji, Kazuki; Shimada, Masakazu; Okada, Yasukazu
Abstract : In group-living animals, social interactions influence various traits including circadian activity. Maternal care, in particular, can have a strong effect on the circadian activity of parents or nurses across taxa. In social insects, nest-mates are known to have diverse activity rhythms; however, what kind of social environment is crucial in shaping an individual's rhythm is largely unknown. Here, we show that the focal brood types being taken care of (i.e. egg, larva and pupa) have significant effects on individual activity/rest rhythm, using the monomorphic ant Diacamma (putative species indicum ). When isolated from a colony, nurses exhibited a clear circadian rhythm. However, when paired with eggs or larvae, they exhibited around-the-clock activity with no apparent rhythm. In contrast, a clear activity rhythm emerged when nurses were paired with a pupa, requiring little care. Such brood-type-specific changes in circadian activity are considered to arise from the difference in caretaking demands. Our finding may contribute to the understanding of the organization of a colony in the context of behavioural variability under different microenvironments.